2017
DOI: 10.5830/cvja-2017-013
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities in treatment-naïve HIV subjects in south-east Nigeria

Abstract: SummaryBackground:Cardiac complications of human immunodeficiency virus (HIV) infection are important causes of morbidity and mortality. We set out to determine the electrocardiographic (ECG) abnormalities in treatment-naïve HIV-positive patients in Enugu, south-east Nigeria.Methods:This was a cross-sectional study involving 250 HIV-positive and 200 HIV-negative subjects. Demographic and anthropometric data, relevant investigations and ECG results were compared between the groups.Results:An abnormal ECG was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 20 publications
2
22
2
Order By: Relevance
“…The prevalence of sinus tachycardia was higher than any other ECG abnormality among HIV patients in this study. This pattern has also been observed in other (11,28). High heart rate has been observed as an independent risk factor for cardiovascular morbidity and mortality in the general population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of sinus tachycardia was higher than any other ECG abnormality among HIV patients in this study. This pattern has also been observed in other (11,28). High heart rate has been observed as an independent risk factor for cardiovascular morbidity and mortality in the general population.…”
Section: Discussionsupporting
confidence: 72%
“…However, such data are not available for Chinese HIV patients who may also experience high prevalence of subclinical atherosclerosis (21). In the present study, we observed relatively high prevalence of sinus tachycardia and ST-T segment elevation in HIV-positive individuals, although the prevalence is slightly lower than that reported by studies in south-east Africa (11) and USA (22,23). Such differences reflect global diversities in a confluence of CVD risk factors that may or may not be directly associated with HIV among PLWH, such as environmental exposures, lifestyle, nutrition, coinfections, access to ART and healthcare continuum (24)(25)(26).…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, 11% of HIV+/ART+ participants in our study presented with abnormal P wave durations. These findings support Okoye and Anyabolu [ 22 ], who showed that 13% of the HIV+ participants presented with abnormal P waves. They also reported that abnormalities in atrial and ventricular electrical activities were more prevalent in HIV+ participants with a lower BMI.…”
Section: Discussionsupporting
confidence: 90%
“…An abnormal ECG was present in 175 (70%) of the 250 treatment-naive HIV-positive subjects, and 70 (35%) of the 200 HIV-negative subjects [27].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%